2016
DOI: 10.3855/jidc.7213
|View full text |Cite
|
Sign up to set email alerts
|

The combined-disk boronic acid test as an accurate strategy for the detection of KPC carbapenemase in Central America

Abstract: Introduction: Carbapenemase-producing Klebsiella pneumoniae (KPC) outbreaks may cause a huge economical burden on developing countries. Furthermore, KPC can be challenging to detect. We describe the laboratory strategy for the detection of KPC from 2011 to 2013 in a tertiary care hospital in Central America with approximately 1,000 beds. Methodology: A retrospective analysis of a clinical laboratory database was done to determine the pragmatic application of the combined-disk boronic acid test during a KPC out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…A study conducted by Ting-ting Qu et al in 2009 showed that CDT also detected other types of carbapenemase including Verona integron-borne metallo- β -lactamase (VIM), which was the most widespread metallo- β -lactamase in P. aeruginosa [41, 42]. Our results for KPC detection using PBA disk test K. pneumoniae (Table 4) were in accordance with findings obtained by Athanasios Tsakris et al (using PBA-400 μ g) [31] and Julio Zúñiga et al (using 300 μ g APBA) [43]. The efficiency of PBA disk test in E. coli was low, particularly in sensitivity and PPV because of the sample size of KPC-producing E. coli , only 3 strains with one of them being a false negative.…”
Section: Resultssupporting
confidence: 90%
“…A study conducted by Ting-ting Qu et al in 2009 showed that CDT also detected other types of carbapenemase including Verona integron-borne metallo- β -lactamase (VIM), which was the most widespread metallo- β -lactamase in P. aeruginosa [41, 42]. Our results for KPC detection using PBA disk test K. pneumoniae (Table 4) were in accordance with findings obtained by Athanasios Tsakris et al (using PBA-400 μ g) [31] and Julio Zúñiga et al (using 300 μ g APBA) [43]. The efficiency of PBA disk test in E. coli was low, particularly in sensitivity and PPV because of the sample size of KPC-producing E. coli , only 3 strains with one of them being a false negative.…”
Section: Resultssupporting
confidence: 90%
“…Also of concern are carbapenemase-producing Klebsiella pneumoniae. There have been many outbreaks in the Latin American region [5], particularly in Panama where there was an outbreak from 2011 to 2013 that was difficult to control [6]. Carbapenemases of the metallo-β-lactamases type, such as NDM-1 and VIM, have also emerged in the region [5, 7].…”
Section: Introductionmentioning
confidence: 99%